DESKRIPSI KESALAHAN SISWA MENGERJAKAN SOAL CERITA MATEMATIKA DI SD - Inaytullah, Kasih Ingati; Hamdani, Hamdani; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the errors of students in working on math word problem at 5th grade in SD Negeri 23 Bekut Tebas Sub-district. The method used is descriptive with the case study research form. Subjects in this study were students of 5th grade in SDN 23 Bekut,Tebas Sub-district, there were 23 people, who were selected to be interviewed were 6 people. Data collection tools in the form of written tests in the form of essays (description) with a total of 4 questions. Based on the results of research students' errors include misconceptions, procedural errors, and miscalculation / carelessness. Calculations for high-level mathematical skills include concept errors of 37.50%, procedure errors of 50.00%, and calculation errors / carelessness of 50.00%. For the level of moderate math ability, it includes 67.31% concept errors, 76.92% procedure errors, and 84.62% calculation / carelessness errors. For the low level of mathematical ability include 75.00% misconception, 87.50% procedure error, and 100.00% calculation / carelessness error. So, it can be concluded that at a high level of mathematical ability, the dominant types of errors are procedural errors and miscalculation / carelessness with the same percentage of 50.00%. While the level of moderate and low mathematical abilities, the most common mistakes are calculation / carelessness, with 84.62% and 100.00%.Â Keywords: Student errors, Math Word Problem, Students Ability Levels.